Os acidentes do trabalho e as doenças ocupacionais no meio ambiente rural e seus impactos judiciais trabalhistas - Cervi, Mauro Luiz (2015)
One of the ways a man has to provide his own subsistence is through work. In the context of the rural area, the Brazilian Law regulated the activity of the agriculture worker by the Law nº 5889, of June 8th, 1973 and by the Decree nº 73626 of February 12th, 1974. Later on, in 1988, in the Federal Constitution, the 7th article equates the rural worker to the urban one in terms of rights. The place where the worker exercises his job may present risks to his physical and psychological integrity. Moreover, the risky attitudes he performs can cause accidents. The accidents at work are directly connected to the activities developed by the human being in order to survive. Since the Stone Age, out of survival, the human beings have created tools in order to make their activities easier. The risks of accident grew significantly after the Industrial Revolution, in the XVIII century. Recently, the exposure of the workers to risks has increased, and so have the number of accident-type; accident-path and diseases related to the working activity. As a consequence of this increase in the number of accidents, the improvement in the access to justice and the worker s awareness, several judicial demands appeared aiming at the repayment of the material, moral or aesthetical damages caused. Thus, this study aims at identifying the main occupational accidents and diseases resulting from work in the rural environment and analyzed the Labor Judicial impacts (Working Claims or Indemnity Claims) and the criteria adopted by the First Instance judges and comparing them to the decisions of the Regional Labor Courts, in the grounding given to the decisions and on the values or indemnities established for material damage (emerging damage and loss of profit), moral damage and aesthetical damage. In order to obtain the data required, we conducted researches in the Labor Departments and in the Regional Labor Courts in eight Brazilian states chosen for being more agriculture oriented. It was concluded that there is a set of criteria for the grounding of material damage. For moral and aesthetical damage the grounding is similar; however, there is divergence in the arbitration of quantum.